Financial Status and Literacy, and Retirement Preparedness of Generation X Government Employees - Leorena Kyla L. Abad; Lady Angelique L. Angelito; Mae D. Arceno; Eligen H Sumicad Jr (Aktiva)
Purpose: To investigate the relationship between financial literacy and retirement preparedness of Generation X government employees. Design/methodology/approach: This study employed a quantitative research design. Specifically, the descriptive-correlational design uses survey data. This allows the exploration of associations between variables without manipulation, offering insights into how these variables interrelate and influence retirement preparedness. A survey was conducted using a questionnaire administered via printed forms. Research Findings: Generation X government employees have high financial literacy but varying levels of retirement preparedness. A significant positive correlation exists between financial literacy and retirement preparedness. Contribution/Originality/Novelty: The study fills the gap in the literature by focusing on a specific demographic, the Generation X government employees in the Philippines.